2019
DOI: 10.1002/hep.30190
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclin‐Dependent Kinase 5

Abstract: Cdk5 inhibition represents an effective approach to improve Sorafenib response and to prevent Sorafenib treatment escape in HCC. Notably, Cdk5 is an addressable target frequently overexpressed in HCC and with Dinaciclib a clinically tested Cdk5 inhibitor is readily available. Thus, our study provides evidence for clinically evaluating the combination of Sorafenib and Dinaciclib to improve the therapeutic situation for advanced-stage HCC patients. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…Consistent with this model, the depletion of CDK5 by shRNA leads to the hyperphosphorylation of IRFBP2, increased IRF2 expression, and lower PD-L1 levels (68,69). In addition, CRISPR-mediated disruption of CDK5 in cancer cells results in suppression of tumor growth (69,70).…”
Section: (V) Cyclin-dependent Kinase 5 (Cdk5)supporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this model, the depletion of CDK5 by shRNA leads to the hyperphosphorylation of IRFBP2, increased IRF2 expression, and lower PD-L1 levels (68,69). In addition, CRISPR-mediated disruption of CDK5 in cancer cells results in suppression of tumor growth (69,70).…”
Section: (V) Cyclin-dependent Kinase 5 (Cdk5)supporting
confidence: 53%
“…Its inhibition confers antitumor immunity due to interference with interferon regulatory factor 2 (IRF2) and interferon regulatory factor-binding protein 2 (IRF2BP2) (66,67). Consistent with this model, the depletion of CDK5 by shRNA leads to the hyperphosphorylation of IRFBP2, increased IRF2 expression, and lower PD-L1 levels (68,69). In addition, CRISPR-mediated disruption of CDK5 in cancer cells results in suppression of tumor growth (69,70).…”
Section: (V) Cyclin-dependent Kinase 5 (Cdk5)mentioning
confidence: 81%
“…Knockdown of METTL3 expression increased the number of autophagosomes and LC3 accumulation in HCC cells, indicating suppression of autophagy may reverse the m 6 A-dependent resistance to sorafenib, a molecular targeted drug that inhibits RAF/ MEK/ERK pathway and VEGFR/PDGFR pathway. Previous studies have reported that combination of anti-ANXA3 (Tong et al, 2018) or Cdk5 inhibition (Ardelt et al, 2019) with sorafenib acts as novel strategies to improve sorafenib response in HCC treatment. We applied combination of autophagy inhibitor with sorafenib for HCC treatment under hypoxia and obtained the significant sensitivity effects of the cells to sorafenib, suggesting another novel strategy for sorafenib-resistant HCC treatment.…”
Section: A Validation Of Biomarker Genes Related To Autophagy In Foxomentioning
confidence: 99%
“…Recently, several research groups have utilized CRISPR-based methods to understand the potential resistance mechanisms and increase the efficacy of sorafenib in hepatocellular carcinoma (HCC). Suppression of cyclin dependent kinase 5 (CDK5) combined with sorafenib resulted in a reduced cell proliferation and migration as well as suppression of HCC progression both in vitro and in vivo by interfering with intracellular trafficking mechanisms [43]. It has been shown that knockout of the fibroblast growth factor receptor (FGFR4) using CRISPR technology sensitizes HCC cancer cells to sorafenib [44].…”
Section: Liver Cancermentioning
confidence: 99%